PENERAPAN PERTANGGUNGJAWABAN PIDANA KORPORASI DALAM BERBAGAI PUTUSAN PENGADILAN - Akbar, Muhammad Fatahillah (UI Scholars Hub, 2021)
By the development of criminal law in Indonesia, the corporate criminal responsibility has been introduced in many Acts. In the practices, there are criminal court decisions which sentenced corporations. This article aims to comprehensively examine how corporate criminal responsibility is implemented in various court decisions. It is found that aggregation theory, which corporate criminal responsibility is based on the actions of some people in the corporation scope, has been applied in most cases. Howeverm the weakness of the aggregation theory, in environment crimes, only corporation which was responsible and most organizers were not. On the other hand, in the corruption cases, the organizers, such as directors, were responsible, even thought they were adjudicated in different examinations. In promoting cheap, efficient, and simple examination, the combination of cases between corporations and directors shall be applied more. Furthermore, the Supreme Court Regulation Number 13 of 2016, the corporate criminal responsibility provision shall be regulated in the Act type, such as in the Bill of Criminal Code.